Synaptic elements for GABAergic feed-forward signaling between HII horizontal cells and blue cone bipolar cells are enriched beneath primate S-cones. - Christian Puller (Public Library of Science (PLoS), 2014)
The functional roles and synaptic features of horizontal cells in the mammalian retina are still controversial. Evidence exists for feedback signaling from horizontal cells to cones and feed-forward signaling from horizontal cells to bipolar cells, but the details of the latter remain elusive. Here, immunohistochemistry and confocal microscopy were used to analyze the expression patterns of the SNARE protein syntaxin-4, the GABA receptor subunits α1 and ρ, and the cation-chloride cotransporters NKCC and KCC2 in the outer plexiform layer of primate retina. In macaque retina, as observed previously in other species, syntaxin-4 was expressed on dendrites and axon terminals of horizontal cells at cone pedicles and rod spherules. At cones, syntaxin-4 appeared densely clustered in two bands, at horizontal cell dendritic tips and at the level of desmosome-like junctions. Interestingly, in the lower band where horizontal cells may synapse directly onto bipolar cells, syntaxin-4 was highly enriched beneath short-wavelength sensitive (S) cones and colocalized with calbindin, a marker for HII horizontal cells. The enrichment at S-cones was not observed in either mouse or ground squirrel. Furthermore, high amounts of both GABA receptor and cation-chloride cotransporter subunits were found beneath primate S-cones. Finally, while syntaxin-4 was expressed by both HI and HII horizontal cell types, the intense clustering and colocalization with calbindin at S-cones indicated an enhanced expression in HII cells. Taken together, GABA receptors beneath cone pedicles, chloride transporters, and syntaxin-4 are putative constituents of a synaptic set of proteins which would be required for a GABA-mediated feed-forward pathway via horizontal cells carrying signals directly from cones to bipolar cells.